Urban growth during civilian and military administrations in Osogbo, Nigeria (2018)
Research on comparative analysis of urban growth and structure during military and civilian regimes most especially in Africa where coup d’etats is common and where land is mainly controlled by private individuals is limited. This study analysed the temporal patterns and morphological characteristics of urban growth during the military and civilian regimes as well as during different civilian administrations using eight landscape metrics. Landsat satellite images of 1984, 1991, 2000, 2003, 2010 and 2014 were used in the analysis. It was found that urban growth occurred primarily through expansion (annexation) of extant urban areas rather than spontaneous and detached development.